Location of lacunar infarcts correlates with cognition in a sample of non-disabled subjects with age-related white-matter changes: the LADIS study. Issue 5 (11th February 2009) - Benisty, S; Gouw, A A; Porcher, R; Madureira, S; Hernandez, K; Poggesi, A; van der Flier, W M; Van Straaten, E C W; Verdelho, A; Ferro, J; Pantoni, L; Inzitari, D; et al.
Abstract : Objectives: In cerebral small vessel disease, white-matter hyperintensities (WMH) and lacunes are both related to cognition. Still, their respective contribution in older people remains unclear. The purpose of this study is to assess the topographic distribution of lacunes and determine whether it has an impact on cognitive functions in a sample of non-disabled patients with age-related white-matter changes. Methods: Data were drawn from the baseline evaluation of the LADIS (Leucoaraioisis and Disability study) cohort of non-disabled subjects beyond 65 years of age. The neuropsychological evaluation was based on the Mini Mental Status Examination (MMSE), a modified Alzheimer Diseases Assessment Scale for global cognitive functions, and compound Z scores for memory, executive functions, speed and motor control. WMH were rated according to the Fazekas scale; the number of lacunes was assessed in the following areas: lobar white matter, putamen/pallidum, thalamus, caudate nucleus, internal/external capsule, infratentorial areas. An analysis of covariance was performed after adjustment for possible confounders. Results: Among 633 subjects, 47% had at least one lacune (31% at least one within basal ganglia). The presence of lacunes in the thalamus was associated with lower scores of MMSE (β = −0.61; p = 0.043), and worse compound scores for speed and motor control (β = −0.25; p = 0.006), executive functions (β = −0.19; p = 0.022) independently of the cognitive impact of WMH. There was also a significant negative association between the presence of lacunes in putamen/pallidum and the memory compound Z score (β = −0.13; p = 0.038). By contrast, no significant negative association was found between cognitive parameters and the presence of lacunes in internal capsule, lobar white matter and caudate nucleus. Conclusion: In non-disabled elderly subjects with leucoaraisosis, the location of lacunes within subcortical grey matter is a determinant of cognitive impairment, independently of the extent of WMH.